ISOLATION, PURIFICATION AND CHARACTERIZATION LIPASE ENZYME FROM BACTERIA ISOLATE OF MANURE COMPOST - SAPUTRA (NIM:20516031), HENDRA
Lipase (triacylglycerol acylhydrolases, EC 3.1.1.3) is an enzyme that catalyze the hydrolysis of ester bond in triacylglicerol and catalyze the transesterification with alcohol. Lipase is a potential biocatalyst for applications in the industrial field such as the food industry, oil and fat industry, pharmacy, cosmetics, detergents, biopolymer and biodiesel. Lipase can be isolated from almost all living things, both higher organisms like animals and plants as well as low organisms such as fungi and microorganisms. Most potential source to isolate lipase is microorganism because their grows faster and more various lipase could be obtained. This microorganisms were isolated from several phase of manure composting. The composting process is a process that converts organic material into a more stable material containing humus through the warm up stage. The composting process has four main phases, namely the initial mesophilic phase, thermophilic phase, mesophilic phase and the final phase of cooling or maturation. The microorganisms found during the composting process will produce enzymes for the decomposition process, one of which is lipase to break down lipids. This study aims to obtain lipase enzymes that have hydrolysis and transesterification activities from catlle manure compost bacteria isolates and identify the lipase-producing bacteria. In this study, 8 potential bacterial isolates were used which had lipase enzyme activity obtained from previous studies. Bacteria with the highest enzyme activity were reproduced in the production media and identified by an ribotyping analysis method of the 16S rRNA gene. Lipase of crude extract from bacterial production was isolated by using partial purification by acetone fractionation and continued by anion exchange chromatography. Lipase enzymes from each stage of purification were characterized using by native-PAGE, SDS-PAGE, zymografi and determined for their hydrolysis and transesterification activities. The activity of purified lipase enzyme was characterized based on biochemical properties including substrate specificity, optimum temperature and optimum pH. The results of the selection of crude bacterial extract activity showed that the isolates with F2E code had the highest hydrolysis activity with a value of 0.165 units/mL (1 activity unit was defined as the number of enzymes that can release 1 μmol product per minute) and transesterification activity of 14.13% (conversion value of the substrate become a product). Chromosomal DNA was isolated and used as a template to amplification 1500 bp of gene 16S rRNA using PCR. The results of alignment nucleotide and phylogenetic analysis showed that F2E isolates had a 99% similarity to Brevibacillus brevis. Production of F2E bacteria was carried out in Luria Bertani liquid medium at a growth temperature of 50 Ã‚Â°C for 15 hours. Partial purification of crude extracts was carried out using acetone fractionation in stages from 0-40%, 40-60%, 60-80% and 80-95%. Native-PAGE, SDS-PAGE and zymogram electroforegrams results showed active lipase from each acetone fractions has a molecular weight of 32 kDa. The acetone fraction with highest specific activity value was at 60-80% fraction with a hydrolysis value of 2.024 units/mg and a transesterification activity of 19.82%. Anion exchange of chromotography purification results obtained 32 kDa active lipase has specific activity of 12.71 units/mg, with purification level of 18.81 times and 6.62% yield. This protein has transesterification activity value of 25.17%. Characterization of the purified lipase enzyme has a high specificity of decanoate substrate (C10) with an optimum temperature of 50 Ã‚Â°C and optimum pH 8 so that this enzyme is suitable to be applied in various industrial fields